A Robotic Mobile Platform for Service Tasks in Cultural Heritage. (10th July 2015) - Carbone, Giuseppe; Tedeschi, Franco; Gallozzi, Arturo; Cigola, Michela
Recently, the preservation and survey of cultural heritage goods is attracting increasing interest from the media. Several famous historical sites seem to require an increased effort to maintain their preservation. Nevertheless, it is very difficult to find sufficient funds and human resources to fulfil these needs. Accordingly, this paper outlines a specific application of service robotics to cultural heritage, with the aim to reduce the required time and costs for surveying and maintaining cultural heritage goods. These applications require careful attention paid to the proper design of a robotic mobile platform with the features necessary to fulfil tasks of architectonic survey and preservation. To this end, specific operation scenarios have been carefully described in order to identify the specific design requirements and constraints that are raised by, for example, the necessity of operation over delicate surfaces, or the presence of unevenness or obstacles. The authors then propose a design solution for a service robot fit for the analysis, survey and conservation of historical sites, as based on the characteristics of the outlined scenarios. A preliminary prototype is also described herewith, in order to show its engineering feasibility in relation to the simulated operation scenarios.